En-bloc resection of bladder tumours (ERBT): current and future perspectives - Struck, J. P.; Kramer, M. W.; Merseburger, A. S.; Hartmann, Arndt; Herrmann, T. R. W. (Aktuelle Urologie, 2017)
Limitations inherent in the conventional transurethral resection of bladder tumours, the standard approach for diagnosis and treatment of bladder cancer, are well known: staging errors due to insufficient resection depth as well as intravesical tumour fragmentation, both of which make histopathological evaluation difficult. The purpose of this review is to present recent clinical data on the en-bloc resection of bladder tumours (ERBT), which has been demonstrated to offer a high potential to overcome these limitations. The recent findings show that ERBT provides a good resection quality with varying detection rates for tunica muscularis, which is a surrogate marker for resection quality regarding muscle-invasive tumours. ERBT can be performed using all energy sources. Available data show no relevant difference with regard to perioperative morbidity compared with cTURB. No conclusions can be drawn regarding the impact of ERBT on recurrence as the data are partly controversial. This has to be defined by further studies.
EVALuna2:6865